Trends Toward Self-Medication Practices During Covid-19 In Gujranwala District: Trends Toward Self-Medication Practices During Covid-19 - Raza, Syed Qasim; Waqar, Muhammad; Ahmad, Shahzad; Iqbal, Hassan; Saifullah, Amna (Pakistan Journal of Health Sciences, 2022)
In Gujranwala, self-medication is a prevalent practice since it offers a low-cost alternative for individuals, and it entails the incorrect and irresponsible use of medications to cure self-recognized symptoms. It is also noteworthy that SM has both positive and negative aspects that affect the life of people. Objectives: To determine the occurrence, pattern, and sources of self-medication among respondents with all socioeconomic statuses and educational levels. Methods: A cross-sectional online survey on 535 residents of the targeted region was undertaken from June to November 2021 in Gujranwala district. We analyze our data by using SPSS and find mean values of our different variables and also find the frequencies and percentages the variables for achievement of our desired results. Results: As COVID-19 preventive, 44 (8.7%) respondents self-medicated with penicillin, and only 4 (0.8%) with paracetamol. When COVID-19 symptoms appeared, the pattern shifted, with azithromycin having the highest rate of self-medication of 49 (9.75%) of all drugs. When people were diagnosed with COVID-19, 12.5% used azithromycin, and 10.3% used penicillin. Conclusions: This study found a significantly high level of SM among men in Gujranwala district. Analgesics, particularly paracetamol and Ibuprofen, were the most often utilized medications for SM.